Analysis Of Justice In The Application Of Legal Sanctions To Traffic Violators Based On The Electronic Ticketing System - Madinah Mokobombang; Nenden Herawaty Suleman; Muhammad Julianto Sumanta; Siti Mahratul Nurjanna Mamonto; Salsa Annisa; Sabil Mokodenseho (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the fairness of the application of legal sanctions to traffic violators through the Electronic Traffic Law Enforcement (ETLE) system using an empirical juridical approach supported by a normative juridical approach. The empirical juridical approach is used to examine the implementation of ETLE in social reality through field observations and interviews with the public, police officers, and road users who have received electronic tickets. Meanwhile, the normative juridical approach is used to examine the legal provisions governing ETLE, such as Law No. 22 of 2009 and police regulations regarding electronic evidence and enforcement procedures. The results of the study indicate that normatively the ETLE system has fulfilled the principles of legal certainty, objectivity, and legality in traffic law enforcement. However, empirically, several obstacles were still found, including a lack of socialization, limited public understanding of the objection mechanism, inconsistencies in vehicle ownership administrative data, and technical constraints on the equipment. Nevertheless, ETLE is considered fairer because it reduces direct interaction between officers and violators and minimizes the potential for irregularities. This study concludes that the conformity between legal norms and field practices still needs to be strengthened so that substantive justice in the ETLE system can be optimally realized.